Accuracy of a self-report prescription opioid use diary for patients discharge from the emergency department with acute pain: a multicentre prospective cohort study. Issue 10 (28th October 2022) - Daoust, Raoul; Paquet, Jean; Williamson, David; Perry, Jeffrey J; Iseppon, Massimiliano; Castonguay, Véronique; Morris, Judy; Cournoyer, Alexis
Abstract : Objectives: Self-reported approaches that assess opioid usage can be subject to social desirability and recall biases that may underestimate actual pill consumption. Our objective was to determine the accuracy of patient self-reported opioid consumption using a 14-day daily paper or electronic diary. Design: Prospective cohort study. Setting: Multicentre study conducted in four Québec (Canada) emergency departments (ED): three university-affiliated centres, two of them Level I trauma centres and one urban community hospital. Participants: ED patients aged ≥18 years with acute pain (≤2 weeks) who were discharged with an opioid prescription. Patients completed a 14-day daily diary (paper or electronic) assessing the quantity of opioids consumed. On diary completion, a random sample from the main cohort was selected for a follow-up visit to the hospital or a virtual video visit where they had to show and count the remaining pills. Patients were blinded to the main objective of the follow-up visit. Outcomes: Quantity of opioid pills consumed during the 2-week follow-up period self-reported in the 14-day diary (paper or electronic) and calculated from remaining pills counted during the follow-up visit. Intraclass correlation coefficient (ICC) and Bland-Altman plots were used to assess accuracy. Results: A total of 166 participants completed the 14-day diary as well as the in-person or virtual visit; 49.4% were women and median age was 47 years (IQR=21). The self-reported consumed quantity of opioid in the 14-day diary and the one calculated from counting remaining opioid pills during the follow-up visit were very similar (ICC=0.992; 95% CI: 0.989 to 0.994). The mean difference between both measures from Bland-Altman analysis was almost zero (0.048 pills; 95% CI: −3.77 to 3.87). Conclusion: Self-reported prescription opioid use in a 14-day diary is an accurate assessment of the quantity of opioids consumed in ED discharged patients. Trial registration number: NCT03953534 .